Innate and Adaptive Immune Response to a Virus: An Integrated Learning Module - Ellen F. Dudrey; Niti Manglik; Veronica Y. Velasco; Dolgor Baatar; Janet F. Piskurich (Association of American Medical Colleges, 2018)
Introduction Medical schools must expand their teaching strategies to address a new generation of medical students and ensure their growth into lifelong, self-directed learners. Integration across basic science disciplines packaged together with clinical medicine produces learning materials that better enable medical students to achieve these goals. Methods We created a narrated audiovisual learning module illustrating the foundational sciences and clinical presentation surrounding immune responses to viral infections. We integrated immunology, microbiology, histology, pathology, and clinical medicine and included a self-assessment quiz and clinical vignette with questions to test students' understanding of the material. We published the module on our school's learning management system and tracked student usage, which was followed by an in-class survey to assess student perceptions of the usefulness of the module. Results Sixty-four (59%) of the first-year medical students used the module. Thirty-seven students completed the in-class survey assessing their perceptions of the module. Over 95% of responders reported that the module helped them learn the new material, identify areas of weakness, understand the big picture for this immune response, and apply the material in a clinical context. Discussion This module illustrates an approach to integrating basic science disciplines in order to facilitate students' understanding of the mechanisms underlying patients' clinical presentations. Survey results indicated that students valued the module as a self-directed learning component that integrated essential clinical concepts. The module was a helpful tool for students to evaluate their comprehension of immunology in a clinical context and can be used as required or optional material.